2005
DOI: 10.1007/s00330-005-0005-4
|View full text |Cite
|
Sign up to set email alerts
|

CT enteroclysis: technique and clinical applications

Abstract: CT enteroclysis: technique and clinical applicationsAbstract CT enteroclysis (CTE) has been gradually evolving with technical developments of spiral and multidetector row CT technology. It has nowadays become a well-defined imaging modality for the evaluation of various small bowel disorders. Volume challenge of 2L of enteral contrast agent administrated to the small bowel via a nasojejunal catheter ensures luminal distension, the prerequisite for the detection of mural abnormalities, also facilitating the acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
8

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 63 publications
1
33
0
8
Order By: Relevance
“…Taking into account that in this patient population enteroclysis stands at the end of the diagnostic chain these are satisfactory results which are consistent with the data of other research groups and justify the use of enteroclysis [24][25][26][27] . None the less investigation of gastrointestinal bleeding remains the domain of endoscopy.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Taking into account that in this patient population enteroclysis stands at the end of the diagnostic chain these are satisfactory results which are consistent with the data of other research groups and justify the use of enteroclysis [24][25][26][27] . None the less investigation of gastrointestinal bleeding remains the domain of endoscopy.…”
Section: Discussionsupporting
confidence: 88%
“…Magnetic resonance imaging (MRI), therefore, is gaining importance by providing direct visualization of mural and extramural changes as well as utilizing multiplanar imaging [2] . Because of the superior soft tissue contrast MRI imaging is superior to computed tomography (CT) concerning enteral pathologies [2,24] . In addition, the absence of radiation exposure, especially among young and very young patients who have to undergo multiple follow-ups for chronic disease monitoring, is of high value.…”
Section: Discussionmentioning
confidence: 99%
“…We are aware that there is no agreement in the literature about the usefulness of performing intestinal preparation before CT examination. Many authors [1,6,11] advise a light diet free of fruit and vegetables for 2 days before CT and the L M Minordi, A Vecchioli, P Mirk and L Bonomo administration of laxatives the day before. A few authors [12,13] advise fasting for 8-12 h prior to CT. We have been recommending our intestinal preparation for radiological study since 1980 and since 2000 for CT examination, and have found that the intestinal loops are usually clean so we plan to continue recommending this preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, las desventajas intrínsecas del método: bajo valor predictivo negativo, operador dependiente, visualización indirecta de la pared y falta de visualización del compromiso extraintestinal entre otras, la han desplazado como técnica diagnóstica (8,9) . La enteroclisis por tomografía computada (E-TC) es hoy en día el método de imágenes de elección en el estudio de patología tumoral y no tumoral de ID (10)(11)(12) . Esta técnica combina las ventajas de la enteroclisis tradicional (adecuada distensión de asas intestinales) con las de la TC multicorte, con el potencial de demostrar en forma simultánea alteraciones intraluminales, murales y extraintestinales.…”
Section: Gastrointestinalunclassified